Amelogenesis Imperfecta: Full Mouth Rehabilitation in Deciduous Dentition - Pinky (Int J Clin Pediatr Dent, 2011)
This clinical report describes the oral rehabilitation of a very young child diagnosed with hypoplastic amelogenesis imperfecta. The specific treatment objectives being adequate patient management, eliminate tooth sensitivity while enhancing esthetics, masticatory function and improved self confidence. The treatment included full mouth rehabilitation with stainless steel crowns on posterior teeth and indirect composite veneers on anterior teeth.